Determinants of Iranian bank profitability - Hassan Ghodrati; Mohammad Ghasemi (Management Science Letters)
Banks are the most important tool for preparing and supplying money in each country. In recent years, by institution of the new private banks and privatization of the governmental banks, banking competition has become very complex. This paper performs an empirical investigation to study the effects of different factors on return on assets and return on equities on 18 selected Iranian firms over the period 2002-2011. Using different regression models, the study studies the effects of total assets, debt ratio, etc. on return of assets (ROA) and return on equities (ROE) on selected eighteen Iranian banks as statistical community. The study considers total assets, ownership ratio, deposits to assets ratio, and loans to assets ratio as independent variables, and ROE and ROA as dependent variables. The results indicate that the private banks returns were better than governmental banks and the commercial banks’ returns were better than special banks. There is a reverse relationship between logarithm of total assets and ownership ratio with profitability based on return of assets.